Cannabis and the Health and Performance of the Elite Athlete. Issue 5 (September 2018) - Ware, Mark A.; Jensen, Dennis; Barrette, Amy; Vernec, Alan; Derman, Wayne
Abstract : Objective: Cannabis (marijuana) is undergoing extensive regulatory review in many global jurisdictions for medical and nonmedical access. Cannabis has potential impact on the health of athletes as well as on performance in both training and in competition. The aim of this general review is to identify and highlight the challenges in interpreting information with respect to elite athletic performance, and to point to important research areas that need to be addressed. Data Sources: A nonsystematic literature review was conducted using Medline and PubMed for articles related to cannabis/marijuana use and sports/athletic performance; abstracts were reviewed by lead author and key themes identified and explored. Main Results: Cannabis may be primarily inhaled or ingested orally for a range of medical and nonmedical reasons; evidence for efficacy is limited but promising for chronic pain management. Although evidence for serious harms from cannabis use on health of athletes is limited, one should be cognizant of the potential for abuse and mental health issues. Although the prevalence of cannabis use among elite athletes is not well-known, use is associated with certain high-risk sports. There is no evidence for cannabis use as a performance-enhancing drug. Conclusions: Medical and nonmedical cannabis use among athletes reflects changing societal and cultural norms and experiences. Although cannabis use is more prevalent in some athletes engaged in high-risk sports, there is no direct evidence of performance-enhancing effects in athletes. The potential beneficial effects of cannabis as part of a pain management protocol, including reducing concussion-related symptoms, deserve further attention.